Green supercapacitor patterned by synthesizing MnO/laser-induced-graphene hetero-nanostructures on wood via femtosecond laser pulses - Young-Ryeul Kim; Han Ku Nam; Younggeun Lee; Dongwook Yang; Truong-Son Dinh Le; Seung-Woo Kim; Sangbaek Park; Young-Jin Kim (Biochar, 2024)
Abstract Eco-friendly next-generation energy storage devices with high energy density are required to meet the increasing demand for sustainable and green electronics. However, their manufacturing requires a lot of chemical precursors and is usually accompanied by chemical waste; it also involves laborious and time-consuming processes such as mixing, heat treating, casting, and drying. Here, we proposed that mass production of microsupercapacitors (MSCs) for green electronics can be achieved by embedding manganese monoxide (MnO) on wood-derived laser-induced-graphene (LIG) via femtosecond laser direct writing (FsLDW) technique. The direct synthesis of MnO/LIG hetero-nanostructures on wood was realized by drop-casting a small amount of precursor between the first and second FsLDW. The preceding FsLDW thermochemically converted wood into LIG while the following FsLDW converted the precursor into MnO, resulting in MnO/LIG hetero-nanostructures. As-fabricated MnO/LIG MSC exhibited enhanced areal capacitance (35.54 mF cm−2 at 10 mV s−1) and capacitance retention (approximately 82.31% after 10,000 cycles) with only a small inclusion of Mn sources (0.66 mg cm−2) and short production time (10 min cm−2), which attributes to operate light-emitting diodes, digital clocks, and electronic paper as well. This approach enables the green, facile, fast, and cost-effective fabrication of future sustainable energy storage devices from biomass for next-generation green electronics. Graphical Abstract